MEDIA BELAJAR PERMAINAN INTERAKTIF BERBASIS POWERPOINT UNTUK SISWA SEKOLAH DASAR - Fauzi, Imam; Ekawati, Nia (LPPM Universitas Putera Batam, 2024)
With the advancement of technology, educational institutions, particularly universities, have begun to implement the use of PowerPoint. However, PowerPoint has not been widely adopted in primary schools. It is essential to understand the benefits and analyze the usage by various institutions that have already integrated it. This analysis focuses on the benefits using an approach that addresses the issues and challenges of PowerPoint as a learning medium. The study provides an overview of the implementation of PowerPoint in educational institutions and offers recommendations for effective utilization.